Inventory of Plant Types to Overcome Vertigo Through Betangas - Ruqiah Ganda Putri Panjaitan; Hayatul Fajri; Gisa Grasilla (Jurnal Penelitian Pendidikan IPA, 2024)
Vertigo is an abnormal feeling characterized by a feeling as if the position of the body and the position of the environment around it are moving when in fact they are not. Vertigo is usually treated with drugs, in Singkawang City vertigo is still treated with the traditional betangas method. Betangas is an activity of taking a steam bath with a mixture of decoctions of plants which has been carried out for generations, betangas is also an indicator for plant preservation. Utilizing and processing plant ingredients to overcome vertigo through betagas, one of which is Singkawang City. This study aims to inventory the types of plants used to treat vertigo through betangas. The method used was interviews with three informants (village shamans), direct observation of areas using betangas in Singkawang City, sampling and data recording, making herbarium and identification processes. The results of the study showed that there were seven types of plants used to treat vertigo through betagas, which included, Basilicum sp. the leaves are used, Dianella sp. the roots are used, Pandanus amaryllifolius Roxb. ex Lindl. the leaves are used, Cymbopogon nardus Linn. the stem part is used, The pucuk used are the roots, geganti used the roots, mensui used the root part of the bark. It can be concluded that plants to overcome vertigo use various types of plants, and for each type a different part is used in betangas.